Etika Melakukan Al-Najwa Menurut Wahbah Az-Zuhaili (Analisis terhadap Penafsiran Surah Al-Mujadalah Ayat 8-10 dalam Tafsir Al-Munir - Hutagalung, Septiana (Lembaga Yasin AlSys, 2023)
The issues raised in this study are how ethics in performing Al-Najwa according to the interpretation of Wahbah Az-Zuhaili in Al-Munir's Tafsir contained in surah Al-Muj is verses 8-10, and the solution in carrying out Al-Najwa actions. While the purpose of this research is to find out the interpretation of Wahbah Az-Zuhaili regarding the ethics of performing Al-Najwa and find out the solution in carrying out the Al-Najwa action. In this study the authors used a qualitative research method (library research) with an interpretation approach, a theological approach. The data collection technique in this study as a whole refers to library sources consisting of commentaries, books, dictionaries, theses, journals or related articles discussing the ethics of conducting Al-Najwa. The results of this study, according to Wahbah Az-Zuhaili, Al-Najwa is a closed secret conversation between two people. The ethics in carrying out Al-Najwa are not carrying out Al-Najwa actions for the purpose of evil, sinful acts, and immorality to the Prophet Muhammad, but carrying out Al-Najwa actions for good purposes, piety to Allah SWT, and if three people are gather, don't let two of them whisper by ignoring the third person, because that will make the third person sad because they feel left out by these two people. The solution in the ethics of carrying out Al-Najwa's actions according to Wahbah Az-Zuhaili is to feel confident that Allah is watching over him, provide knowledge about ethics in conducting secret talks, and put your trust in Allah SWT. and ask Him for protection and help.